Management of Diabetes Mellitus in Patients with Chronic Liver Diseases. (14th December 2019) - Zhao, Yingying; Xing, Huichun; Wang, Xiaomei; Ou, Weini; Zhao, Hong; Li, Ben; Li, Yue; Duan, Ying; Zhuang, Liwei; Li, Wei; Cheng, Danying; Quan, Min; et al.
Abstract : Diabetes mellitus (DM) is a common chronic disease affecting humans globally. During the last few years, the incidence of diabetes has increased and has received more attention. In addition to growing DM populations, DM complications are involving injuries to more organs, such as the heart and cerebral vessel damage. DM complications can reduce quality of life and shorten life spans and eventually also impede social and economic development. Therefore, effective measures to curb the occurrence and development of diabetes assist in improving patients' quality of life, delay the progression of DM in the population, and ease a social burden. The liver is regarded as an important link in the management and control of DM, including the alleviation of glucose metabolism and lipid metabolism and others via glucose storage and endogenous glucose generation from glycogen stored in the liver. Liver cirrhosis is a very common chronic disease, which often lowers the quality of life and decreases life expectancy. According to a growing body of research, diabetes shows a close correlation with hepatitis, liver cirrhosis, and liver cancer. Moreover, coexistence of liver complications would accelerate the deterioration of patients with diabetes. Liver cirrhosis and diabetes influence each other. Thus, in addition to pharmacological treatments and lifestyle interventions, effective control of cirrhosis might assist in a better management of diabetes. When it comes to different etiologies of liver cirrhosis, different therapeutic methods, such as antiviral treatment, may be more effective. Effective control of cirrhosis might be a strategy for better management of diabetes.